The Relationship of Clinical, Cognitive and Social Measures in Schizophrenia: A Preliminary Finding Combining Measures in Probands and Relatives - David Huepe; Rodrigo Riveros; Facundo Manes; Blas Couto; Esteban Hurtado; Marcelo Cetkovich; Maria Escobar; Viviana Vergara; Teresa Parrao; Agustin Ibañez (Behavioural Neurology)
This study examines performance of schizophrenia patients, unaffected relatives and controls in social cognition, cognitive and psychiatric scales looking for possible markers of vulnerability in schizophrenia. Performance of schizophrenia patients from multiplex families, first-degree relatives, and matched controls was compared and, subsequently, discriminant analysis method was used for identifying the best predictors for group membership. By using Multigroup Discriminant Analyses on the three groups, the best predictors were PANSS, Premorbid Adjustment Scale, Faux Pas test, and a face/emotion categorizing task. This model obtained 82% correct global classification, suggesting that the combination of psychiatric scales and neuropsychological/social cognition tesks are the best approach for characterizing this disease. Although preliminary, our results suggest that social cognition tasks are robust markers of schizophrenia family impairments, and that combining clinical, social and neuropsychological measures is the best approach to asses patients and relatives vulnerability.